Mood disorders systematic medication management - Rush, A. John 1942- (Karger, 1997)
This volume provides up-to-date, scientifically-based alternative treatment algorithms for various kinds of mood disorders. It is one of the first publications to enunciate stepwise, specified pharmacological management procedures recommended for major depressive, bipolar, and dysthymic disorders. In addition, it indicates the role for special forms of treatment for depression, including light and electroconvulsive therapies, based on published peer-reviewed scientific literature and extensive in-depth clinical experience.It will be of particular interest to psychiatric residents, internists, family physicians, general practitioners, nurses, medical students and other mental health professionals who are committed to a scientifically based approach to the management of patients with mood disorders
Keywords: Pharmacology; Pharmaceutics; Psychiatry; Gerontology / Geriatrics; Hospital Administration; Nursing; Psychopharmakotherapie; Psychische Störung; Aufsatzsammlung